Creating an intimate community in classroom: reducing students’ level of communication apprehension through group work learning strategies - Sahar, Rafidah; Abdullah, Nur Nabilah (2010)
This research study investigated the effectiveness of group work learning strategy during class lectures and discussion to promote active participation, boost self-confidence and higher course achievement among undergraduates studying at the Centre for Foundation Studies, International Islamic University Malaysia (IIUM). Students were exposed to variety of strategies that incorporated the essence of group work learning to reduce student’s anxiety in oral communication. Students’ communication apprehension scores were compared between the beginning and the end of the course. The results of this study illustrated that there was no significant differences observed between the scores of male and female students and the five different degree programs. However, there were significant differences in the scores between the pretest and posttest results. The results illustrated that in general the students’ level of anxiety was reduced significantly from a very high level of apprehension to a modestly high level of communication apprehension. The results also exhibited that the students were less apprehensive in all four communication setting and the most anxiety-inducing setting was public speaking, whereas the least anxiety-inducing setting was group discussion. Thus, the results revealed that group work learning strategy can improve students’ level of communication apprehension, which in turns encouraged them to partake in communicative activities, thus enhancing their learning.